Impact of the Elimination of Defamation and Fake News Articles in the Criminal Code on Press Freedom and Government Accountability - Flora, Heny Saida; Salmon, Harly Clifford Jonas (Jurnal Hukum dan Keadilan, 2025)
This research explores the impact of the elimination of defamation and fake news articles in the revised Indonesian Criminal Code (KUHP) on press freedom and government accountability. The study employs a qualitative descriptive approach to examine the perspectives of journalists, government officials, and civil society activists concerning how legal reform influences the dynamics between media and the state. Data were collected through in-depth interviews, document analysis, and non-participatory observation, then analyzed using Miles and Huberman's interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the removal of defamation and fake news articles has expanded press freedom and reduced the risk of criminalization against journalists in Indonesia. It signifies a progressive step toward strengthening democratic governance and legal protection of human rights, particularly the right to express and access information. However, the reform also presents new ethical challenges, as the absence of penal provisions may increase the spread of misinformation if not accompanied by strong media ethics and accountability mechanisms. In conclusion, the legal reform marks a significant transition from a restrictive legal culture to one that promotes freedom with responsibility. The study recommends the enhancement of journalistic ethics training, public media literacy, and stronger institutional collaboration between the Press Council, government, and civil society to sustain a balanced and accountable media ecosystem.